Human leukocyte antigen-DRB1 position 11 residues are a common protective marker for sarcoidosis - Foley, P J; McGrath, D S; Puscinska, E; Petrek, M; Kolek, V; Drabek, J; Lympany, P A; Pantelidis, P; Welsh, K I; Zielinski, J; du Bois, R M (American journal of respiratory cell and molecular biology, 2001)
Genetic factors, in particular human leukocyte antigens (HLAs) are important determinants of susceptibility to sarcoidosis, a chronic granulomatous disease of undetermined etiology. To clarify the role of HLA in sarcoidosis we determined HLA-DR and -DQ alleles in case-control samples from three European populations (United Kingdom, Czech, and Polish) and compared these results with those published for three additional populations (Italian, Japanese, and Scandinavian) to determine whether the HLA-DR and/or -DQ alleles act as ethnic-dependent, or ethnic-independent modifiers of disease risk. Although variations were apparent in the alleles associated with susceptibility, reductions in the frequency of alleles associated with protection were remarkably consistent in the six populations. Previously detected associations between single-nucleotide polymorphisms at the TAP2 locus and sarcoidosis were shown to be due to linkage disequilibrium with the HLA-DR locus. The protective HLA-DR alleles, which encode the DR1 and DR4 antigens, were found to share characteristic small hydrophobic residues at position 11, which were replaced by small hydrophilic residues in the remaining, nonprotective, HLA-DR alleles. This residue position is within a pocket of the HLA-DR complex antigen binding groove (designated P6), where it is the only variable amino acid and therefore determines the peptide binding preferences of this pocket. A highly significant reduction in the frequency of individuals carrying HLA-DR alleles with a hydrophobic residue at position 11 was observed in the sarcoidosis cases in the three populations we examined. This suggests this HLA-DR residue is an important protective marker in sarcoidosis.
Keywords: alely; Genetic Markers; Poland; genotyp; Alleles; ABC transportér podrodiny B, člen 3; ATP-Binding Cassette Transporters; Male; HLA-DR Antigens; Genotype; Česká republika; Sarcoidosis, Pulmonary; plicní sarkoidóza; Middle Aged; Genes, MHC Class II; mužské pohlaví; studie případů a kontrol; geny MHC třídy II; Spojené království; Adult; HLA-DRB1 Chains; Czech Republic; Polsko; HLA-DR antigeny; ATP Binding Cassette Transporter, Subfamily B, Member 3; ženské pohlaví; Humans; HLA-DRB1 řetězec; lidé středního věku; United Kingdom; ABC transportéry; dospělí; Female; genetické markery; lidé; Case-Control Studies